Segmental differences found in aqueous angiographic-determined high - and low-flow regions of human trabecular meshwork. (July 2020) - Saraswathy, Sindhu; Bogarin, Thania; Barron, Ernesto; Francis, Brian A.; Tan, James C.H.; Weinreb, Robert N.; Huang, Alex S.
Abstract: This work sought to compare aqueous angiographic segmental patterns with bead-based methods which directly visualize segmental trabecular meshwork (TM) tracer trapping. Additionally, segmental protein expression differences between aqueous angiographic-derived low- and high-outflow human TM regions were evaluated. Post-mortem human eyes (One Legacy and San Diego eye banks; n = 15) were perfused with fluorescent tracers (fluorescein [2.5%], indocyanine green [0.4%], and/or fluorescent microspheres). After angiographic imaging (Spectralis HRA+OCT; Heidelberg Engineering), peri-limbal low- and high-angiographic flow regions were marked. Aqueous angiographic segmental outflow patterns were similar to fluorescent microsphere TM trapping segmental patterns. TM was dissected from low- and high-flow areas and processed for immunofluorescence or Western blot and compared. Versican expression was relatively elevated in low-flow regions while MMP3 and collagen VI were relatively elevated in high-flow regions. TGF-β2, thrombospondin-1, TGF-β receptor1, and TGF-β downstream proteins such as α-smooth muscle actin were relatively elevated in low-flow regions. Additionally, fibronectin (FN) levels were unchanged, but the EDA isoform (FN-EDA) that is associated with fibrosis was relatively elevated in low-flow regions. These results show that segmental aqueous angiographic patterns are reflective of underlying TM molecular characteristics and demonstrate increased pro-fibrotic activation in low-flow regions. Thus, we provide evidence that aqueous angiography outflow visualization, the only tracer outflow imaging method available to clinicians, is in part representative of TM biology. Highlights: Aqueous Angiography (AA) is capable of visualizing segmental aqueous humor outflow (AHO) in living human eyes. AA segmental AHO patterns matched that of bead-based methods which trapper tracers in the trabecular meshwork (TM). AA-determined high- and low-flow TM regions showed segmental changes in pro-fibrotic markers.